The effects of prenatal deaths on national life expectancy: case study U.S.A. - Hollman , Madeleine R.; Pearce, Joshua (Interdisciplinary Journal of Epidemiology and Public Health, 2024)
Introduction: It is a positive indicator that human lifeexpectancies calculated from birth have been increasing. The current standards for counting life-years, however, assume social desirability and exclude all prenatal deaths. These assumptions mask low life-year deaths and obscure results of medical and environmental interventions, thus falsely indicating higher life expectancies.Aim: To quantify the life expectancy with and withoutsocial desirability.Methods: This case study investigates 1930 to 2016 using CDC and World Bank data for the U.S. for the impact of social desirability on life expectancy.Results: It is evident, published U.S. life expectancies are greatly exaggerated and what would have beenshort-lived Americans are disproportionately labeled as socially-undesirable and ignored when counting life years, thus presenting an overly-optimistic view of U.S. health.Conclusions: A comprehensive global investigation isneeded, and a refinement of life expectancy calculationsshould be introduced, which does not bias results by only counting life expectancy from the time of live birth.